The Influence of Work-Life Balance and Motivation on Employee Performance Across All Districts in The Island of Sebatik - Octhaniaz, Cynthia; Hamzah, Djabir; Hendragunawan (PT. Maju Malaqbi Makkarana, 2023)
The purpose of this study is to analyze the influence of work-life balance on employee performance The purpose of this study is to analyze the influence of work-life balance on employee performance with motivation as a moderator. The study aims to determine and analyze whether motivation plays a role in improving employee performance across all districts in the island of Sebatik, as well as to determine and analyze whether motivation moderates the relationship between work-life balance and employee performance in all districts in the island of Sebatik. The research method used in this study is quantitative research. The population in this study consists of all Civil Servants in all districts on the island of Sebatik, totaling 110 employees. The sampling method used is census technique, which includes all 110 elements being investigated. Therefore, it analyzes all objects, all indicators, all events, and incidents. The data used in this study is primary data, collected through the distribution of questionnaires. The data analysis technique used in this study is quantitative data analysis using statistical methods. The statistical method used is Partial Least Square (PLS). The research findings indicate that there is a significant positive influence of motivation on improving employee performance across all districts in the island of Sebatik. However, motivation does not moderate the relationship between work-life balance and employee performance in all districts on the island of Sebatik. Therefore, motivation is not a moderating variable in this study. This means that motivation cannot strengthen or weaken the relationship between work-life balance and employee performance.